The Potential Effects of Implementing an Antibiotic Stewardship Program by Integrating It with Medication Therapy Service in a Low-Income Serving Clinic - A Single-Center Experience - Arinze Nkemdirim Okere; Miquetta L. Trimble; Vassiki Sanogo; Ukamaka Smith; Clyde Brown; Sarah G. Buxbaum (University of Minnesota Libraries Publishing, 2022)
Background: Bacterial antimicrobial resistance (AMR) is a leading cause of mortality worldwide. Although AMR is common in low-income communities, there is limited evidence of the effect of antibiotic stewardship programs in low-income communities in the United States. Objectives: Our goal is to assess the effects of implementing pharmacist-led ASP by integrating it with medication therapy management service (MTM) in a low-income serving clinic. We evaluated the following 1) antibiotic prescriptions per 1000 patients, 2) the frequency of clinic (office) visits 30-day post-index clinic visits for recurring infections. Methods:  To achieve our goal, we conducted a pre-post, quasi-experimental intervention study using an interrupted time-series analysis to assess the following: 1) antibiotic prescriptions per 1000 patients and the 2) frequency of office visits (including telehealth) within 30-day post-index clinic visits associated with recurrent infection. Results: Our findings revealed that the long-term effect of our antibiotic stewardship program intervention was associated with 63.69% reduction in antibiotic prescriptions per 1000 patients (change in slope = -0.173, [95% CI: (-0.30, -0.05)], P < 0.007) and a reduction in the frequency of office visits within  30-day post-index clinic visits by  67.27% (change in slope = -2.043, [95% CI: (-3.84, -0.24)], P < 0.028). Conclusion: Implementing antibiotic stewardship programs is feasible for clinics serving low-income populations. It was associated with a reduction in antibiotic prescriptions and preventable clinic (office) visits within 30 days due to infection recurrence.